EFEKTIVITAS FUNGSI KINERJA TERHADAP PELAYANAN PUBLIK PADA BAGIAN HUMAS SEKRETARIAT DAERAH KABUPATEN SIGI - Abdullah, Dewi Cahyawaty (Katalogis, 2020)
The reseach aims: 1) to find out the effectiveness of performance function to public service on public relationship division at regional secretariate of Sigi regency. 2) to find out barrier factors and support factors and its alternative solution. The research was basically survey and the type was descriptive quantitative. The sample was selected using purposive sampling technique. The population was 100 people with sample numbered 31 people. The author used a survey method using frequency table and percentage. The research findings show that indicator of physical ability, menthal and emotion, high work motivation, knowledge, acuracy, and friendliness are already well while indicator of skill fastness is still unwell because of the barrier. The barrier factors are where the officers have not owned a specific skill and inavailability of the facility.